Advancing Sustainable Textile Metrology: Reflectivity Measurement with Controlled Light Sources - Radostina A. Angelova; Elena Borisova; Daniela Sofronova (Applied Sciences)
This study introduces an experimental method for evaluating the reflectivity of flexible textile materials under controlled lighting conditions. The proposed methodology employs a light booth and four standard illuminants (D65, TL84, Incandescent light A, and Department store light CWF), as well as a fixed-position lux meter to assess the reflective properties of textile samples with different knitted macrostructures. Each sample is measured against a black background, and reflectance is quantified as a ratio between the light intensity measured with and without the sample in place. The approach is especially relevant for the textile industry, as it provides valuable insights into the development of sustainable reflective materials for protective clothing and wearable technologies. By offering a repeatable, low-cost measurement technique, this method advances textile metrology, contributing to the optimization of material selection based on reflectivity needs and ensuring reliability across different lighting environments. This research supports the creation of more efficient, sustainable, and adaptive textiles.